Keefektifan setting TPS dalam pendekatan discovery learning dan problem-based learning pada pembelajaran materi lingkaran SMP - Rahmi Hidayati (Jurnal Riset Pendidikan Matematika, 2017)
Penelitian ini bertujuan untuk mendeskripsikan keefektifan setting TPS dalam pendekatan discovery learning dan problem based learning terhadap prestasi belajar, kemampuan komunikasi matematis, dan kemampuan interpersonal siswa. Jenis penelitian ini adalah quasi eksperiment dengan pretest-posttest nonequivalent group design. Sampel penelitian dipilih secara acak dari delapan kelas yang ada, terpilih dua kelas. Instrumen yang digunakan adalah tes prestasi belajar, tes kemampuan komunikasi matematis, dan angket kemampuan interpersonal. Untuk menguji keefektifan setting TPS dalam pendekatan discovery learning dan problem-based learning data dianalisis menggunakan uji one sample t-test. Untuk menguji perbedaan keefektifan, data dianalisis menggunakan MANOVA. Hasil penelitian menunjukkan bahwa setting TPS dalam pendekatan discovery learning dan problem-based learning efektif terhadap prestasi belajar, kemampuan komunikasi matematis, dan kemampuan interpersonal siswa. Tidak terdapat perbedaan keefektifan setting TPS dalam pendekatan discovery learning dengan problem based learning ditinjau dari aspek prestasi belajar, kemampuan komunikasi matematis, dan kemampuan interpersonal siswa.Kata Kunci: setting TPS, pendekatan discovery learning, pendekatan problem-based learning, prestasi belajar, kemampuan komunikasi matematis, kemampuan interpersonal The Effectiveness of Setting Think Pair Share in Discovery Learning Approach and Problem-Based Learning in Circle of Junior High School Students AbstractThe purpose of this study was to describe the effectiveness of setting Think Pair Share (TPS) in the approach to discovery learning and problem-based learning in terms of student achievement, mathematical communication skills, and interpersonal skills of the student.  This study was a quasi-experimental study using the pretest-posttest nonequivalent group design. The research population comprised all Year VIII students of SMP Negeri 1 Yogyakarta. The research sample was randomly selected from eight classes, two classes were elected. The instrument used in this study is the learning achievement test, a test of mathematical communication skills, and interpersonal skills student questionnaires. To test the effectiveness of setting Think Pair Share (TPS) in the approach to discovery learning and problem-based learning, the one sample t-test was carried out. Then, to investigate the difference in effectiveness between the setting Think Pair Share (TPS) in the approach to discovery learning and problem-based learning, the Multivariate Analysis of Variance (MANOVA) was carried out. The research findings indicate that the setting TPS discovery approach to learning and problem-based approach to learning (PBL) is effective in terms of learning achievement, mathematical communication skills, and interpersonal skills of the students. No difference in effectiveness between setting TPS discovery approach to learning and problem-based learning (PBL) in terms of learning achievement, mathematical communication skills, and interpersonal skills of the students.Keywords: TPS setting in discovery learning approach, in problem-based learning, academic achievement, mathematical communication skills, and interpersonal skills of the student